Intervener trustworthiness predicts cooperation with conservation interventions in an elephant conflict public goods game. Issue 4 (26th July 2020) - Baynham‐Herd, Zachary; Bunnefeld, Nils; Molony, Thomas; Redpath, Steve; Keane, Aidan
Abstract: Conservation conflicts exist in complex socio‐ecological systems and are damaging to both people and wildlife. There is much interest in designing interventions to manage them more effectively, but the importance of who does the intervening remains underexplored. In particular, conflicts are influenced by perceptions of the trustworthiness of natural resource managers and conservation organizations. However, experimental studies of how the different facets of trustworthiness shape responses to interventions are rare in conflict settings. We develop an experimental, framed public goods game to test how support for otherwise identical elephant conflict interventions varies with perceptions of the trustworthiness of two different intervening groups—a community group or a conservation organization—and compare game behaviour to pre‐ and post‐game interviews. Results from three agro‐pastoral communities ( n = 212 participants) in northern Tanzania show that participants cooperate more with interveners they perceive to be more trustworthy. Results also suggest that different aspects of trustworthiness matter differentially—with perceptions of interveners' integrity and benevolence more strongly predicting cooperation than perceptions of their ability. The findings suggest that trust‐building and greater consideration of who is best placed to intervene in conflicts may help improve natural resource management and increase stakeholder support for conservation interventions. This study also further demonstrates how experimental games offer opportunities to test behaviour change interventions and help to inform evidence‐based conservation. A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article.